Sustainable social development of municipalities located in national park and their environmental protection - Pawłat-Zawrzykraj, Agata; Podawca, Konrad (Ecological Questions, 2013)
Development of social infrastructure of rural areas and conservation of environmental valuable areas are one of the main objectives of local and national authorities. The main research problem presented in the article is to analyze the spatial accessibility of social infrastructure (understood as a 1st level service, such as: in case of education - kindergarten, primary and junior high schools, in case of health-care - health centers and clinics; in case of security - fire department and police) by local residents of the Izabelin Municipality located within the boundaries of the Kampinoski National Park.